Against Ahok: An Analysis of Emotion-Driven Movements and Network Power in Jakarta’s 2017 Gubernatorial Election - Priyadharma, Subekti W. (Salasika, 2018)
Many Indonesian citizens reacted angrily to part of Basuki Tjahaja Purnama’s, popularly known as Ahok, video uploaded by Buni Yani to his Facebook account on October 6, 2016. The video was taken during a speech in Kepulauan Seribu where Ahok, the Governor of Jakarta, quoted one verse of Al-Qur'an, Surah Al-Maidah verse 51. Some people were filled with outrage because of Ahok’s statement, but some others were angry because, one week prior to now Yani’s infamous Facebook status, Yani added his own ‘frame’ to that clip. In that status, Yani said, with a question mark, that Ahok had defamed the religion of Islam. It caused the polarization of Indonesian civil society: pro-Ahok bloc, who believed that his words were not an insult to the holy scriptures and anti-Ahok bloc, who strongly argued that Ahok, a Christian of Chinese descent and has no Javanese root in his blood – a minority in 3 categories –, had no right to cite Quranic verses and therefore despised Islam. Consequently, he deserved to be criminalized and deposed from his Governor post. Using Affective Intelligence theory and Manuel Castells’ Network Theory of Power, this paper attempts to analyze the character of both anti-Ahok movement and its counter-movement. While affective intelligence theory centers the effect of affection on political behavior, the network theory of power focuses more on how networks empower individuals to act as a collective entity against the dominant power. The materials for this analysis are obtained mainly from the internet.